Experimental Study of Management Systems for Emission Reduction in Ignition Engines - Fekari, A.; Javani, N.; Jafarmadar, S. (MATERIALS & ENERGY RESEARCH CENTER-MERC, 2020)
The present study aims to investigate the amount of exhaust gases emissions of a 4-cylinder gasoline-ignition engine. An experimental study of an ignition engine management system has been conducted for emissions optimization, using Winols specialized software. In order to achieve a steady state conditions in the experiments, the temperature of the water and engine oil before each test reached the engine's working temperature (90 degrees C) to allow various parts of the engine to remain stable and the tests are performed in in-line engine operation. Two sets of tests with idle (850-900 rpm) and mid-range (2500 rpm) are considered. Experiments were performed for three identical engines with different mileages and obtained results were discussed. According to the obtained results, after applying changes to the engine management system, a 22% reduction in the unburned hydrocarbon emission in both cases was obtained. Furthermore, it is found that 31 and 5% reduction in carbon monoxide emissions in the idle and mid-range were obtained, respectively. As a result of applying these changes, there was a reduction of 1.4% in NOx emission in the idle case and a decrease in about 19% at 2500 rpm.
Keywords: Engine Management System; Exhaust Gases; Exhaust Gases Emission; Spark Advance; PERFORMANCE; FUMIGATION; GASOLINE; FUEL; Engineering